Tingkat Kesesuaian Kinerja dan Harapan Pelanggan pada Terminal Peti Kemas Tanjung Priok - Marthaleina Ruminda Sitorus; Tedy Herdian; Fransisco Lambert (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
Tanjung Priok Container Terminal is a terminal that serves the loading and unloading process of containers with high service performance standards. Termnal Container customers expect the performance of the services provided by the company to meet their satisfaction or expectations. This study aims to determine the level of conformity between service performance and customer satisfaction or expectations at the container terminal. This study analyzed the data of 67 Container Terminal customers obtained by providing a questionnaire to the customers. The results of the suitability level analysis show that the service performance provided by the container terminal management is satisfied or very satisfied because it has a conformity percentage of 91.93%, besides that the index value of the gap or gap between performance and customer satisfaction / expectations is at -0.28. Where at this value, Container Terminals generally have met customer expectations, but in terms of reliability and assurance, it is still necessary to improve so that it is expected to increase the number and loyalty of Container Terminal customers.